2011
DOI: 10.1007/s12070-010-0061-1
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Approach to Fisch Stage II to III-b Juvenile Nasopharyngeal Angiofibroma

Abstract: Juvenile nasopharyngeal angiofibroma (JNA) are locally growing highly vascular tumours treated primarily by surgical excision (open approach as wide as a mid facial degloving or endoscopic approach). All our patients underwent exclusive endoscopic tumour excision after a pre-operative embolisation. The tumours were completely resected with acceptable blood loss and no recurrences or residual masses were seen. Post-operative morbidity was minimal without external scar-marks. To conclude endoscopic excision is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…4,5 With the evolution of endoscopic techniques, it has now become possible to successfully resect also class III tumors less invasively. 6 Various studies recently showed that the endoscopic technique seems to be superior not only regarding morbidity but also in visualization of persisting tumor tissue, blood loss, time spent in the hospital, and recurrences. 7,8 Although surgical techniques are evolved, the resection of JNA remains a demanding task that requires surgical expertise.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 With the evolution of endoscopic techniques, it has now become possible to successfully resect also class III tumors less invasively. 6 Various studies recently showed that the endoscopic technique seems to be superior not only regarding morbidity but also in visualization of persisting tumor tissue, blood loss, time spent in the hospital, and recurrences. 7,8 Although surgical techniques are evolved, the resection of JNA remains a demanding task that requires surgical expertise.…”
Section: Introductionmentioning
confidence: 99%
“…The patient presents with recurrent epistaxis and nasal blockage with intranasal mass, cheek swelling, visual changes, hearing impairment and neurological deficits may be present sometimes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Various management options for control of JNA, include surgery, radiotherapy, chemotherapy, hormonal therapy and electrocoagulation. Surgery remains the mainstay of treatment [4]. Surgical approaches range from extensive mid facial degloving to minimally invasive transnasal endoscopic excision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It occurs almost exclusively in adolescent males and forms 0.05% of all head and neck neoplasms [1,2]. This decade has witnessed a new armamentarium of diagnostic techniques that have revolutionized the management of JNA.…”
Section: Introductionmentioning
confidence: 99%